Computational postprocessing quantification of small bowel motility using magnetic resonance images in clinical practice: An initial experience - Åkerman, André; Månsson, Sven; Fork, Frans-Thomas; Leander, Peter; Ekberg, Olle; Taylor, Stuart; Menys, Alex; Ohlsson, Bodil (Journal of magnetic resonance imaging, 2016)
Purpose To study the feasibility and to gauge the potential clinical impact of quantifying small bowel motility using magnetic resonance imaging (MRI) in a larger population with a spectra of gastrointestinal conditions with impaired small bowel motility. Materials and Methods Data were gathered retrospectively from a cohort of 127 patients undergoing MR enterography (1.5 Tesla) in 2011. Cine motility sequences were processed with validated motility analysis software and a parametric motility map was generated. Regions of interests were drawn in the jejunum, ileum, and terminal ileum, and Jacobian standard deviation mean motility index' score (MIS) was calculated. Patients were divided into Crohn's disease (CD), ulcerative colitis, irritable bowel syndrome, and healthy subjects. Results In CD, terminal ileum motility was lower in comparison to healthy subjects (mean difference: ‐0.1052 arbitrary units, 95% confidence interval: ‐0.1981–‐0.0122, P = 0.018). Subgrouping of CD showed that the difference was recognized in patients with disease limited to the small bowel (mean difference: ‐0.1440 arbitrary units, 95% confidence interval: −0.2491–‐0.0389, P = 0.002). Visible dysmotility of terminal ileum on MRI reflected a reduced MIS compared with normal motility (0.22 ± 0.09 and 0.33 ± 0.15 arbitrary units, respectively, P = 0.043). Motility correlated negatively between ileum and age (P = 0.021), and between terminal ileum and C‐reactive protein in ulcerative colitis (P = 0.031). Conclusion Motility quantitation revealed a significant difference in motility of terminal ileum in patients with small bowel CD compared with healthy subjects, concording with visible dysmotility and inflammatory changes. J. Magn. Reson. Imaging 2016;44:277–287.